Research of Trajectory Control Algorithms for a Robotic Manipulator - Irina Vasilenko; Anastasiia Vediakova (Современные информационные технологии и IT-образование, 2022)
Industrial robots are widely used in manufacturing and their application field is constantly expanding. The movement along a given trajectory is one of the most common modes of robotic manipulators’ operation. The paper presents a comparative analysis of four trajectory control schemes, three are PD (proportional-derivative) controllers, and the last one is based on a sliding mode. Using the three-link robot-manipulator model, a simulation modeling complex was developed using the MATLAB Simulink, which allows conducting computational experiments with the closed-loop control system of the manipulator. With that complex, the performance of the considered control schemes was investigated. The effect of parametric perturbations in the manipulator model and signal disturbances, such as a white noise, high frequency harmonic signal, random single interference were studied. Methodical recommendations were formulated for the controller’s application and tuning. The considered control schemes are applicable to various robots of series kinematics.